2007
DOI: 10.1152/physiolgenomics.00291.2005
|View full text |Cite
|
Sign up to set email alerts
|

Temporal analysis of E2 transcriptional induction of PTP and MKP and downregulation of IGF-I pathway key components in the mouse uterus

Abstract: Temporal analysis of E2 transcriptional induction of PTP and MKP and downregulation of IGF-I pathway key components in the mouse uterus. Physiol Genomics 29: 13-23, 2007; doi:10.1152 doi:10. /physiolgenomics.00291.2005 is well known to be associated with uterine cancer, endometriosis, and leiomyomas. Although insulin-like growth factor I (IGF-I) has been identified as a mediator of the uterotrophic effect of E2 in several studies, this mechanism is still not well understood. In the present study, identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 71 publications
2
30
0
Order By: Relevance
“…Other studies in IGF1-null mutant mice showed that IGF1 is necessary for epithelial cells of prepubertal uteri in response to E 2 to progress through G 2 but not for their traverse through G 1 (23). In a recent transcriptome analysis, the transcripts of multiple genes associated with the IGF1 pathway were affected in response to E 2 , further suggesting that this pathway is regulated by this hormone (24).…”
Section: Discussionmentioning
confidence: 96%
“…Other studies in IGF1-null mutant mice showed that IGF1 is necessary for epithelial cells of prepubertal uteri in response to E 2 to progress through G 2 but not for their traverse through G 1 (23). In a recent transcriptome analysis, the transcripts of multiple genes associated with the IGF1 pathway were affected in response to E 2 , further suggesting that this pathway is regulated by this hormone (24).…”
Section: Discussionmentioning
confidence: 96%
“…Both hormones, particularly E2 after 4h, provoke a major influx of fluid into the uterus, and this increased vascular permeability is in part due to an increased mRNA expression of the vascular endothelial growth factor (VEGF) [18]. Indeed, in our previous studies VEGF mRNA expression was up-regulated by 6.7-fold and 3-fold at 3h following E2 or DHT administration, respectively [4,20], which supports its involvement in the regulation of vascular permeability.…”
Section: Discussionmentioning
confidence: 60%
“…The quality of RNA was analyzed on an Agilent 2100 Bioanalyzer (Agilent Technologies Inc, Santa Clara, CA). First-strand cDNA synthesis was accomplished using 5 µg of isolated RNA as reported previously [20]. The resulting products were purified with QIA quick PCR purification kits (QIAGEN, Valencia, CA).…”
Section: Quantitative Real -Time Pcr (Qrt-pcr)mentioning
confidence: 99%
See 2 more Smart Citations